Dimensions and Factors of Contemporary Geography Learning Climate at Senior High School - Mukminan Mukminan (Faculty of Geography, Universitas Gadjah Mada, 2018)
This study develops the dimensions and factors of the learning climate of contemporary geography at the senior high school through the process of Exploratory Factor Analysis (EFA). This research uses Research and Development (R & D). Research respondents involved 595 experts and practitioners of geography learning in Yogyakarta, determined using stratified-purposive sampling. The calculation results give the average value of Aiken logical validity of 0.85, the value of Measure of Sampling Adequacy of 0.789, Bartlett's test of sphericity 0.000 <0. 05, a Chi square of 37.6 with df=25, p. value=0.05061, RMSEA of 0.058 <0.08, and a t value of 4.78 > 1.96 and with a significance level of 5%. These calculations have been eligible for EFA analyses. The results classify the geography learning climate into four dimensions with 16 factors. The dimensions are: (1) Student-centered learning, (2) positive relationships among students, (3) positive relationships between teachers and students, and (4) developing and strengthening classroom rules. Each dimension consists of 6, 4, 2, and 4 factors.